2022
DOI: 10.1111/1346-8138.16323
|View full text |Cite
|
Sign up to set email alerts
|

Mannan‐binding lectin exacerbates the severity of psoriasis by promoting plasmacytoid dendritic cell differentiation via the signal transducer and activator of transcription 3–interferon regulatory factor 8 axis

Abstract: Psoriasis is a chronic inflammatory skin disease mediated by host immune responses. Plasmacytoid dendritic cells (pDC) and interferon (IFN)‐α secreted by pDC are involved in the initiation of psoriasis. Mannan‐binding lectin (MBL), a vital component of the complement pathway, plays a critical role in innate immune defense and the inflammatory response. Our previous study found that MBL could exacerbate skin inflammation in psoriatic mice, but the effect of MBL on pDC remains unstudied. Herein, we revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…One study found that MBL may aggravate psoriatic skin inflammation by assisting the infiltration of the neutrophils in psoriatic lesions (58). Another study revealed that psoriasis patients displayed higher MBL levels than control subjects and that the level of MBL correlated positively with PASI score and psoriasis severity, and found that MBL assisted the differentiating and infiltrating processes of plasmacytoid dendritic cells in initial skin lesions of psoriasis, leading to the aggravation of disease severity (59). Therefore, the reason for the lack of protective effect with MBL-deficient genotypes needs to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that MBL may aggravate psoriatic skin inflammation by assisting the infiltration of the neutrophils in psoriatic lesions (58). Another study revealed that psoriasis patients displayed higher MBL levels than control subjects and that the level of MBL correlated positively with PASI score and psoriasis severity, and found that MBL assisted the differentiating and infiltrating processes of plasmacytoid dendritic cells in initial skin lesions of psoriasis, leading to the aggravation of disease severity (59). Therefore, the reason for the lack of protective effect with MBL-deficient genotypes needs to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory properties of MBL include the suppression of pro-inflammatory cytokines and the inhibition of T cell proliferation through calreticulin. On the other hand, pro-inflammatory effects of MBL have also been shown, as it increases the IL-1β, IL-6 and IFNγ production of mature human dendritic cells (DCs) [106] and enhances the plasmacytoid-to-DC differentiation and their pro-inflammatory cytokine production [107]. MBL also induces pro-inflammatory responses in platelets [108] and in corneal epithelial cells [109], where the involvement of IL-1 signaling is a common factor in both studies.…”
Section: Cellular Effects Of Prmsmentioning
confidence: 99%